Thyrotrophin receptor antibody concentration and activity, several years after treatment for Graves’ disease - Nalla, Preethi; Young, Stuart; Sanders, Jane; Carter, Joanne; Adlan, Mohamed A.; Kabelis, Katarzyna; Chen, Shu; Furmaniak, Jadwiga; Rees Smith, Bernard; Premawardhana, Lakdasa D. K. E. (Clinical endocrinology (Oxford), 2019)
Summary Objective TSH receptor antibodies (TRAb) are responsible for autoimmune hyperthyroid disease (Graves’ disease; GD) with TRAb levels tending to decrease following treatment. Measurement of TRAb activity during follow‐up could prove valuable to better understand treatment effectiveness. Study design TRAb concentration and stimulating (TSAb) and blocking (TSBAb) activity of patient serum were assessed following different treatment modalities and follow‐up length. Methods Sixty‐six subjects were recruited following treatment with carbimazole (n = 26), radioiodine (n = 27) or surgery (n = 13). TRAb, TPOAb, TgAb and GADAb were measured at a follow‐up visit as well as bioassays of TSAb and TSBAb activity. Results Forty‐five per cent of all patients remained TRAb‐positive for more than one year and 23% for more than 5 years after diagnosis, irrespective of treatment method. Overall, TRAb concentration fell from a median (IQR) of 6.25 (3.9‐12.7) to 0.65 (0.38‐3.2) U/L. Surgery conferred the largest fall in TRAb concentration from 11.4 (6.7‐29) to 0.58 (0.4‐1.4) U/L. Seventy per cent of TRAb‐positive patients were positive for TSAb, and one patient (3%) was positive for TSBAb. TRAb and TSAb correlated well (r = 0.83). In addition, 38/66 patients were TgAb‐positive, 47/66 were TPOAb‐positive and 6/66 were GADAb‐positive at follow‐up. Conclusions TRAb levels generally decreased after treatment but persisted for over 5 years in some patients. TRAb activity was predominantly stimulatory, with only one patient demonstrating TSBAb. A large proportion of patients were TgAb/TPOAb‐positive at follow‐up. All treatment modalities reduced TRAb concentrations; however, surgery was most effective.